2006
DOI: 10.1007/bf03327752
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological features of patients with prolonged anorexia nervosa as assessed by the Minnesota Multiphasic Personality Inventory

Abstract: AN patients whose illness duration was prolonged characteristically had more hysteria with family conflict. This should be considered in their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…From a clinical standpoint, it could be difficult to diagnose as organic or functional a gastrointestinal disease referred by ED patients; anyway it is well-known that ED patients’ body sensations – often inappropriately experienced – can influence the disease and its course [11]. Moreover, in this subgroup were also clearly represented some conversion symptoms, only sporadically discussed in AN patients [76,77]. Hence, it should be considered that for some AN patients – as in this cluster - body language can be a further sign of their clinical severity, requiring a clinical approach specifically tailored to these conversion aspects, often a neglected issue in AN treatment.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical standpoint, it could be difficult to diagnose as organic or functional a gastrointestinal disease referred by ED patients; anyway it is well-known that ED patients’ body sensations – often inappropriately experienced – can influence the disease and its course [11]. Moreover, in this subgroup were also clearly represented some conversion symptoms, only sporadically discussed in AN patients [76,77]. Hence, it should be considered that for some AN patients – as in this cluster - body language can be a further sign of their clinical severity, requiring a clinical approach specifically tailored to these conversion aspects, often a neglected issue in AN treatment.…”
Section: Discussionmentioning
confidence: 99%
“…They can be applied in a group or in an individual manner. Among these possible techniques, postural exercises are recommended to be included in the treatment because a relationship exists between the duration and severity of the eating disorder and the possibility of reporting lower back pain [234]. In this way, patients with prolonged anorexia present postural disorders mainly due to the low muscle tone and weakness that promote posture compensations (e.g., scoliosis) and lower back pain [235].…”
Section: Physical Therapy Interventionsmentioning
confidence: 99%
“…Additionally, family therapy was less effective than individual therapy among patients with early-onset AN that lasted over 3 years [9]. Nozaki et al reported that inpatients with a longer duration of AN manifested higher levels of hysteria and low back pain according to responses from the Minnesota Multiphasic Personality Inventory [10]. Furthermore, it has been reported that patients with a longer duration of AN show more deterioration of cardiac sympathovagal balance and renal function [11, 12].…”
Section: Introductionmentioning
confidence: 99%